Web enable integrated information system for a plastic injection mould manufacturing company - Singaram Ravi. (2008)
A multinational plastic injection mould manufacturing company is no exception. Divisions such as sales, CAD, CAM and tool room, located in different countries, have to work as a team in every mould design project. Therefore, information sharing and communication between them impact the progress of mould manufacturing. This dissertation explores ways to integrate information flow in such a mould making company. A web-enabled intranet was chosen as the solution and implemented. A suitable web-programming tool, Active Server Pages (ASP), was used to create user-friendly and secure web pages. An easy-to-use database tool, Microsoft Access, was chosen to implement the database side of this intranet. Many mould-making companies are using Pro/Engineer in their CAD and CAM departments for a long time. Therefore, there is a great potential to systematically store and access this experience as knowledgebase using the intranet. This dissertation has a dedicated section for tapping this Pro/Engineer knowledgebase.